2015
DOI: 10.2478/aoas-2014-0080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variety and Plant Protection Method on Chemical Composition and in Vitro Digestibility of Faba Bean (Vicia Faba) Seeds

Abstract: The aim of the work was to determine the effect of faba bean varieties and plant protection method on their yield of seeds and protein, chemical composition, in vitro true digestibility (IVTD) and nutritive value for ruminant feeding. The study was carried out on four cultivars of faba beans grown in similar environmental conditions in a two-factorial field experiment. The variation between cultivars, modified by the plant protection method, in chemical composition and IVTD of seeds may suggest that there woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
4
10
1
Order By: Relevance
“…FB seeds contain 210-341 g/kg dry matter (DM), with globulins (61.35% crude protein [CP]) and albumin (20.02% CP) being the major components (Gasim et al, 2015). The total carbohydrate content of FB seeds ranges from 457 to 701 g/kg DM, with starch, total sugars, and fiber TA B L E 1 The proximate nutritional content (g/kg dry matter, unless otherwise stated) of faba bean seeds summarized from several references a (Aguilera et al, 1992;Azaza et al, 2009;Barłóg et al, 2019;Benchaar et al, 1994;Berger et al, 1999;Cherif et al, 2018;Cucci et al, 2019;Dixon & Hosking, 1992;Elsheikh et al, 1999;Ferruzzi et al, 2009;Gous, 2011;Hadjipanaiotou et al, 1985;Hejdysz et al, 2016;Ivarsson & Neil, 2018;Kumar et al, 2015;Lamminen et al, 2019;Masoero et al, 2005;Micek et al, 2015;Morales et al, 2008;Moujahed et al, 2020;Rotger et al, 2006;Rubio et al, 1992;Skylas et al, 2019;Smith et al, 2013;Soltanzadeh et al, 2017;Vaga et al, 2017;Zagorakis et al, 2015 as the major carbohydrate components (Khan et al, 2015;Morales et al, 2008). In addition, FB seeds are also good sources of dietary minerals (Cazzato et al, 2014), notably potassium, phosphorus, iron, and zinc, while iron and zinc are essential for the sustenance and optimal physiological function of both humans and livestock (Bailey et al, 2015).…”
Section: Proximate Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…FB seeds contain 210-341 g/kg dry matter (DM), with globulins (61.35% crude protein [CP]) and albumin (20.02% CP) being the major components (Gasim et al, 2015). The total carbohydrate content of FB seeds ranges from 457 to 701 g/kg DM, with starch, total sugars, and fiber TA B L E 1 The proximate nutritional content (g/kg dry matter, unless otherwise stated) of faba bean seeds summarized from several references a (Aguilera et al, 1992;Azaza et al, 2009;Barłóg et al, 2019;Benchaar et al, 1994;Berger et al, 1999;Cherif et al, 2018;Cucci et al, 2019;Dixon & Hosking, 1992;Elsheikh et al, 1999;Ferruzzi et al, 2009;Gous, 2011;Hadjipanaiotou et al, 1985;Hejdysz et al, 2016;Ivarsson & Neil, 2018;Kumar et al, 2015;Lamminen et al, 2019;Masoero et al, 2005;Micek et al, 2015;Morales et al, 2008;Moujahed et al, 2020;Rotger et al, 2006;Rubio et al, 1992;Skylas et al, 2019;Smith et al, 2013;Soltanzadeh et al, 2017;Vaga et al, 2017;Zagorakis et al, 2015 as the major carbohydrate components (Khan et al, 2015;Morales et al, 2008). In addition, FB seeds are also good sources of dietary minerals (Cazzato et al, 2014), notably potassium, phosphorus, iron, and zinc, while iron and zinc are essential for the sustenance and optimal physiological function of both humans and livestock (Bailey et al, 2015).…”
Section: Proximate Nutrientsmentioning
confidence: 99%
“…The gross energy and metabolizable energy (ME) contents of FB seeds, which range from 14.69 to 19.70 MJ/kg DM and from 11.30 to 13.80 MJ/kg DM, respectively. The chemical composition content of FB seeds is highly dependent on the genotypes/cultivars and environmental conditions, as well as agricultural management practices (Ivarsson & Neil, 2018 ; Micek et al., 2015 ; Pelagalli et al., 2020 ; Skylas et al., 2019 ). Compared with general grains such as rice, corn and wheat, FB seeds contain higher CP, dietary fiber, potassium, iron, and folic acid contents (Howard et al, 2018 ; Gu et al., 2020 ).…”
Section: Nutritional Composition Of the Faba Beanmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cultivars adapted to climate conditions of the region are available for seed production including Minica, Metissa, Primo, and Baie-Saint-Paul (Pilote et al, 2017). Variation in chemical composition between FB cultivars has been reported to be small (Micek et al, 2015). Among these cultivars, the Baie-Saint-Paul cultivar is more widely grown in the region of Saguenay-Lac-Saint-Jean because it is most adapted to climate conditions and has the highest yield (6.3 t/ha) compared with other cultivars (Provencher, 1984;Pilote et al, 2017).…”
Section: Chemical Composition Of Fbmentioning
confidence: 99%
“…Contrary to our results, Vaga et al (2017) found that high temperature and longer treatment period compared to our study increase the concentration of NDF in beans. In addition to that, Micek et al (2015) showed that NDF and crude protein content of faba bean is largely related to the cultivar.…”
Section: Resultsmentioning
confidence: 90%